Verwendung von Isocyanaten und ihren Additionsprodukten - Fritz Schmidt (CHIMIA)
Isocyanates are used in dyestuffs and as an ingredient of textile auxiliaries. On hides and skins, hexamethylene diisocyanate ensures excellent white tannage. The addition products of diisocyanates and bivalent alcohols are interesting thermoplastic materials which are used as fibres, films, and injection-moulded articles. Linear high-molecular polyesterpolyurethanes serve the production of high-quality adhesives. Polyisocyanates have gained considerable importance in the rubber field where they are used to promote adhesion to fabrics to be proofed as well as in rubber-to-metal bonding and to achieve other difficult bonds. Crosslinked polyurethanes are obtained from di- or polyisocyanates in combination with linear or branched polyhydroxyl compounds. This ensures coating compositions of very high performance which can be adjusted to the particular application; the compositions are suitable for interior and exterior  finishes, as well as for stoving, electrical insulating and rubber finishes. The most important and still increasing outlet for the polyaddition products of the isocyanates with polyhydroxyl-esters, -ethers and -thioethers are elastomers of flexible to rigid formulation and flexible or rigid foams for many applications, e. g. machinery components, household appliances, upholstering, etc.